An updated concept and revised composition for Hamacreadium Linton, 1910 (Opecoelidae: Plagioporinae) clarifies a previously obscured pattern of host-specificity among species - Martin, Storm B.; Cutmore, Scott C.; Ward, Selina; Cribb, Thomas H. (Zootaxa, 2017)
The present concept of the trematode genus Hamacreadium Linton, 1910 encompasses considerable morphological variability and includes species reported from a broad range of fishes. These include herbivores and planktivores, despite the life-cycle of the type-species, Hamacreadium mutabile Linton, 1910, being known to use fishes as intermediate hosts. Reports of H. mutabile are numerous, spanning the west Atlantic, east Pacific and Indo-west Pacific, whereas other nominal species are infrequently reported and several inadequately described. Following a comprehensive review, a strict revised morphological definition is proposed for the genus. Several nominal species are excluded, but, conversely, finer distinctions are recognised among the species concluded to genuinely belong in the genus. Justified records for species retained in the genus are overwhelmingly from fishes of the families Lutjanidae Gill (snappers) and Lethrinidae Bonaparte (emperors), revealing a previously concealed pattern of host-specificity. For H. mutabile, it is argued that only records from western Atlantic lutjanid fishes should be considered genuine; those from plausible Indo-Pacific fishes most likely represent different species. In addition to H. mutabile, eight species are recognised: Hamacreadium cribbi Bray & Justine, 2016, Hamacreadium hainanense Shen, 1990, Hamacreadium interruptum Nagaty, 1941, Hamacreadium lethrini Yamaguti, 1934, Hamacreadium longivesiculum (Yamaguti, 1952) n. comb., Hamacreadium lutiani (Shen, 1990) n. comb., Hamacreadium morgani Baz,1946 and Hamacreadium phyllorchis (Bilqees, 1976) Cribb, 2005. A key to species of Hamacreadium and comprehensive lists of all host-locality records are included.